The Role of Family Social Control on Sexual Harassment Cases in Tanjungpinang City - Khoirun Nisa; Nika Purnama Sari; Joana Evelin (Journal of Legal and Cultural Analytics, 2022)
Articles 81 and 82 of Undang-Undang Perlindungan Anak of sexual abuse against children are sentenced to a maximum of 15 years. Children are often victims of sexual abuse. The author this time discusses a case of sexual harassment that occurred in Sei Serai village, Kecamatan Bukit Bestari anjungpinang City on May 2, 2022. The harassment started with the owner of a stall in Sei Serai village, Kecamatan Bukit Bestari namely, with the initials Na. He is depicted showing his vitals to the victim, besides that the perpetrator also groped the victim. It didn't stop there, the victim was also invited to watch pornographic videos. The habit of perpetrators who often watch pornographic videos is very likely to increase their sex hormones. Total data in 2022 shows there are 243 cases, with this number showing an increase from the previous year's 174 cases. In addition, with the increasing number of sexual harassment in Tanjungpinang City, one of the underlying factors is low social control. According to Travis Hirci, there are four elements of social control, namely attachment, commitment, involvement and belief, the purpose of which is to regulate individuals or perpetrators so that they do not engage in deviant behavior such as sexual abuse of children.